(untitled) (Hoboken, N.J., 2005)
Gardner's Commercially Important Chemicals: Synonyms, Trade Names, and Properties: Contains 4,174 chemical entries and information such as structure, molecular formula, and chemical name; Includes synonyms for each chemical, including other identifiers, chemical names, trade names, and trivial names, in English and other languages; Provides chemical properties of the compounds, information concerning known uses of the chemical and biological data-in particular, acute toxicity in various species, where available; Lists the companies that manufacture or supply the listed chemicals; Describes bulk inorganic chemicals, major pesticides (herbicides, insecticides, antifungal agents, etc.), and many dyestuffs, surfactants, and metals, along with the most commonly used drugs; Contains indexes by chemical name and synonym, Chemical Abstracts Service (CAS) Registry Numbers, and EINECS (European Inventory of Existing Commercial Substances) numbers.
Keywords: Chemicals,Chemicals,Chemicals; Trademarks